Transformasi Digital untuk Financial Services Menuju Era Society 5.0 - Maghfiroh . Yanuarti; Krisnaldy .; M. Gandung (Jurnal Lokabmas Kreatif : Loyalitas Kreatifitas Abdi Masyarakat Kreatif, 2022)
The development of information and communications technology (ICT) has had a drastic impact on society and industry. Digital transformation generates new values and is a pillar of industrial policy in many countries around the world. In anticipation of this global trend, “Society 5.0″ was introduced as the main or core concept in the 5th Basic Plan of Science and Technology, which was adopted by the Cabinet of Japan in January 2016. The Era of Society 5.0 was identified as part of one of the growth strategies in Japan. We are now in a new era, where globalization and the rapid evolution of digital technologies such as Artificial Intelligence (AI), Internet of Things (IoT) and robotics are bringing significant changes to citizens. Citizens' environments and values are becoming increasingly diverse and complex. Chart 1 below shows activity targeting new digital technologies worldwide, which includes Industry 4.0, also known as “4th Industrial Revolution”, Internet technology industry, and Made in China 2025.Keywords: Society, MSME,5.0